HOTEL EMPLOYEE PERFORMANCE IN NEW NORMAL PERIOD - Yos Horta Meliala; Rialdo Rezeky Manogari Lumban Toruan; Muhammad Saifulloh (Universitas prof. Dr. Moestopo (Beragama), 2022)
This research aims to examine the effect of Transformational Leadership and Organizational Commitment on Employee Performance as well as the mediating effect of Organizational Commitment between Transformational Leadership on affecting Employee Performance in non-star hotels in Medan (North Sumatra) during the “New Normal” period. This is a survey research, using all employees who work in two non-star hotels in the city of Medan (North Sumatra) as research sample, totaling 60 Employees. The results are described descriptively in which were processed using SPSS version 23.0. The mediation variable test was carried out using the Sobel Test with significance level of p <.05. The results showed that there is a positive and significant direct effect of Transformational Leadership and Organizational Commitment on Employee Performance partially. Similarly, simultaneously there is an indirect effect of Transformational Leadership on Employee Performance mediated by Organizational Commitment or in other words Organizational Commitment is able to mediate the effect of Transformational Leadership on Employee Performance. The results of this study prove that the conceptions of Transformational Leadership and Organizational Commitment are still relevant today and also contribute to improve employee performance in the hotel industry in Indonesia, especially non-star hotels in Medan (North Sumatra) in New Normal period. Thus we purpose further research to be conducted to examine worker commitments trough factor analysis approach. Meanwhile, working climate or culture in said characteristic can be describe trough ethnography